Paradigma Pendidikan Agama Kristen Terhadap Etis Dan Norma Guru Sebagai Teladan Pendidik - Mega, Mega; Fernando, Andreas; Saragih, Teguh Parluhutan (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
Christian Religious Education is education that contains teaching Christian values to students. This teaching is certainly centered on Christ as an example and is based on the Bible as a guide. The purpose of this study is to find out how the paradigm of Christian Religious Education regarding teacher ethics and norms. It is important for a teacher to know the ethics and norms of the teacher as a reference in teaching. Because a teacher is a figure who is used as an example by students, both inside and outside the school environment. Unconsciously, the attitude, behavior, and speech of a teacher in the learning process have an influence on students. By knowing the ethics and norms of teachers, a teacher, especially Christian Religious Education teachers can understand and implement them in everyday life. The method in this research is qualitative with literature study. Research data obtained by analyzing data from journals and books. With the result that in Christian Religious Education, teachers must be able to understand and implement the ethics and norms of a teacher in order to be an example.AbstrakPendidikan Agama Kristen adalah pendidikan yang berisi pengajaran nilai-nilai Kristiani kepada siswa. Pengajaran ini tentunya berpusat kepada Kristus sebagai teladan dan didasarkan pada Alkitab sebagai pedomannya. Tujuan penelitian ini yaitu untuk mengetahui bagaimana paradigma Pendidikan Agama Kristen mengenai etis dan norma guru. Penting bagi seorang guru untuk mengetahui etis dan norma guru sebagai acuan dalam mengajar. Karena seorang guru adalah sosok yang dijadikan teladan oleh siswa, baik didalam maupun luar lingkungan sekolah. Secara tidak sadar, sikap, perilaku, dan tutur kata seorang guru dalam proses pembelajaran memberikan pengaruh dalam diri siswa. Dengan mengetahui etis dan norma guru, seorang guru, terutama guru Pendidikan Agama Kristen dapat memahami dan mengimplementasikannya dalam kehidupan sehari-hari. Metode dalam penelitian ini yaitu kualitatif dengan studi literatur. Data penelitian didapatkan dengan cara analisa data dari jurnal-jurnal dan buku-buku. Dengan hasil bahwa dalam Pendidikan Agama Kristen, guru harus mampu memahami dan mengimplementasikan etis dan norma seorang guru untuk bisa menjadi teladan.